The Effect of Transparency, Accountability, Supervision, and Community Participation on Budget Management - Desi Kirana Putri (Perkumpulan Praktisi Akuntansi Indonesia, 2022)
Public sector accounting is accounting used by a public institution or an organization to account for what has been done to the public. One part of the public sector is the Regional Planning and Development Agency (BAPPEDA). Bappeda in carrying out good budget management must apply the principles of transparency, accountability, supervision and community participation. This study aims to determine the effect of transparency, accountability, supervision and community participation on the management of the budget for assistance to the poor. The population in this study were all employees of Bappeda Situbondo Regency. The sampling technique used was purposive sampling with primary data collection by distributing questionnaires according to the criteria of the research sample. The total research sample according to the researcher's criteria is 40 respondents. The data analysis method used is quantitative research with descriptive statistical testing, data instrument testing, classical assumption testing and hypothesis testing. The results of this study indicate that there is a insignificant effect of the variables of transparency, accountability and public participation on the management of the budget for assistance to the poor, while for the supervision variable there is a significant influence on the management of the budget for assistance to the poor.